Antimalarial polyoxygenated and prenylated xanthones from the leaves and branches of Garcinia mckeaniana - Auranwiwat C. (2017)
© 2016 Elsevier Ltd The first phytochemical investigation of the leaf and branch extracts of Garcinia mckeaniana has led to the isolation and characterization of five new polyoxygenated and prenylated xanthones, mckeanianones A-E (1–5), and one new biflavone, mckeaniabiflavone (6), together with 13 known compounds (7–19). The diprenylated pyrano-xanthones (1–3) and the biflavone (6) were isolated from the leaves while the monoprenylated xanthones (4 and 5) were isolated from the branches. The structures of all isolated compounds were elucidated based on spectroscopic methods and were evaluated for their antimalarial activities against the Plasmodium falciparum strains, TM4 (drug sensitive strain) and K1 (a multidrug resistant strain), and cytotoxicity against a Vero cell line (African green monkey kidney epithelial cells). The pyrano-xanthones (1–3, 7 and 8), having two isoprene units, were generally the most active compounds with IC 50 values in the range of 6.0±1.1 _ 8.5±1.2 and 3.6±1.7 _ 7.3±1.2 μM, respectively against the TM4 and K1 strains. Of these compounds 2, 3 and 8 were 2–5 times less cytotoxic against a Vero cell line (IC 50 values of 12.6±0.9, 29.5±3.9 and 13.2±4.6 μM, respectively) in comparison with their antiplasmodial activities.